2013
DOI: 10.1021/am402128s
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Modified Graphene Oxide for Glioma-Targeted Drug Delivery: In Vitro and in Vivo Evaluations

Abstract: Transferrin (Tf), an iron-transporting serum glycoprotein that binds to receptors overexpressed at the surface of glioma cells, was chosen as the ligand to develop Tf-conjugated PEGylated nanoscaled graphene oxide (GO) for loading and glioma targeting delivery of anticancer drug doxorubicin (Dox) (Tf-PEG-GO-Dox). Tf-GO with lateral dimensions of 100-400 nm exhibited a Dox loading ratio up to 115.4%. Compared with Dox-loaded PEGylated GO (PEG-GO-Dox) and free Dox, Tf-PEG-GO-Dox displayed greater intracellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(93 citation statements)
references
References 36 publications
3
89
0
1
Order By: Relevance
“…30 In our experiment, intravenously administered DNR-Tet-Tf-NPs dramatically inhibited the growth of transplantable tumor. DNR-Tet-Tf-NPs have properties to act as NDDS to improve drug concentration in cells; furthermore, Tf-modified NPs has been explored as a target to deliver therapeutics into cancer cells due to their increased expression on malignant cells and accessibility on the cell surface.…”
mentioning
confidence: 51%
“…30 In our experiment, intravenously administered DNR-Tet-Tf-NPs dramatically inhibited the growth of transplantable tumor. DNR-Tet-Tf-NPs have properties to act as NDDS to improve drug concentration in cells; furthermore, Tf-modified NPs has been explored as a target to deliver therapeutics into cancer cells due to their increased expression on malignant cells and accessibility on the cell surface.…”
mentioning
confidence: 51%
“…Transferrin-conjugated polyethylene glycolated GO was demonstrated as an efficient nanovector for the targeted delivery of anticancer drugs to brain tumors both in in vitro and in vivo conditions. 21, 22 Cheng et al showed a novel pH-sensitive nanostructured antitumor drug from a GO-CONH-Schiff base compound in which chitosanxanthone Schiff base and GO acted as the tumor inhibitor and drug delivery carrier, respectively. 21 GO is used as a precursor for reduced GO (rGO) as it is strongly hydrophilic and generates stable and homogeneous colloidal suspensions of negatively charged GO sheets in aqueous and polar organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al synthesized Tf conjugated PEGylated nanographene oxide composites loaded with doxorubicin (Tf-PEG-GODox) for targeted delivery of drug to glioma cells. 25 The nanocomposites showed a drug loading ratio of up to 115.4% and demonstrated signi¯cantly higher cytotoxicity against gliomas as compared to free drug and PEG-GO-Dox, both in in vitro and in vivo (Fig. 2(ii)).…”
Section: Targeted Drug Deliverymentioning
confidence: 96%